(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Relevance of the study. It is known that stress has an immunomodulatory effect associated with an increased risk of developing infections, tumors and autoimmune conditions, but despite the number of consistent studies in this regard, it is possible to fully understand the essence of immunomodulation that causes stress there is no possibility.